(untitled) (Scientica Education Journal, 2024)
Nature education has great potential in forming emotional connections between students and their environment. In today’s educational context, where urbanization and modernization are increasingly dominant, it is important to refocus on direct experiences in nature. Through this approach, students not only learn about ecosystems and biodiversity, but also develop a sense of empathy and responsibility towards the environment. Direct experiences, such as camping, exploring the forest, or doing conservation projects, provide opportunities for students to actively engage with nature. This study aims to explore how nature education can strengthen students’ emotional ties to their surroundings. Using the Systematic Literature Review (SLR) method, this study analyzes various existing literatures to understand the impact of nature education on students’ attitudes and behaviors. The findings of this study indicate that experiences in nature not only increase environmental awareness but also create a deeper connection between students and nature. Students who engage in nature education tend to show positive attitudes towards environmental conservation and are more active in conservation activities. In addition, these experiences can also improve students’ mental health by reducing stress and increasing emotional well-being. Thus, nature education not only functions as an educational tool, but also as a medium to form a generation that is more concerned and responsible for the environment, which is very important amidst the environmental challenges faced today.